Dinamika Perubahan Dasar dan Tebing Sungai Jambu: Studi Kasus pada Sekitar Jembatan Cikuya - Aulia, Humam; Nugroho, Eka; Legowo, Sri; Kusmulyono, Agus Suprapto (JURNAL TEKNIK HIDRAULIK, 2024)
Several cross-sections of the Jambu River, particularly around the Cikuya Bridge, have experienced bank collapse phenomena. This paper interprets the issues related to bank collapse and its impact on the flow capacity of the Jambu River, especially around the Cikuya Bridge. Morphological changes were simulated using a sediment transport model implemented in the Hydrologic Engineering Center's River Analysis System (HEC-RAS) 6.3.1, integrated with the ARS-USDA Bank Stability and Toe Erosion Model (BSTEM). The simulation results indicate that over a period of 10 years, the thalweg elevation (the lowest point of a riverbed)  of the Jambu River around the Cikuya Bridge is predicted to experience deposition in 17 cross-sections and erosion in 15 cross-sections. The highest deposition occurs at the cross-section below the Cikuya Bridge, with a thalweg elevation change of 0.59 m. This warrants attention as the storage capacity of the cross-section decreases by 7% from the initial condition. Predictions indicate that bank collapse will occur in 7 cross-sections over the next 10 years. This is attributed to the steep slopes of silt and clay banks, exceeding 45 degrees, and the reduced safety factor of bank stability due to groundwater pressure influenced by river discharge fluctuations and tidal effects reaching the Jambu River. Bank collapse impacts the elevation change of the riverbed and adds load to the sediment transport model from the collapsing cross-sections to the downstream sections. Keywords:  Jambu River, Cikuya Bridge, Cilacap, sediment transport, bank stability and toe erosion model